Evaluating Biodentine: A Review of Current Research and Clinical Findings - Dr. Srilakshmi J; Dr. Vaishali Sharma; Dr. Poorva Sharma; Dr. Indrajeet Deshpande; Dr. Siddiq Ahmed; Dr. Mohammed Shammas (The Bioscan, 2025)
Biodentine is a bioactive dentin substitute increasingly utilized in restorative and endodontic dentistry. This review evaluates its properties, including mechanical strength, biocompatibility, and dentin regeneration capabilities. While Biodentine presents numerous advantages, such as effective pulp capping, challenges related to handling and long-term performance remain. Current research findings are synthesized to provide a comprehensive overview of Biodentine’s clinical efficacy and its potential future applications in dental practice.